An erythroid enhancer of BCL11A subject to genetic variation determines fetal hemoglobin level - Bauer, Daniel E; Kamran, Sophia C; Lessard, Samuel; Xu, Jian; Fujiwara, Yuko; Lin, Carrie; Shao, Zhen; Canver, Matthew C; Smith, Elenoe C; Pinello, Luca; Sabo, Peter J; Vierstra, Jeff; et al. (Science (American Association for the Advancement of Science), 2013)
Genome-wide association studies (GWASs) have ascertained numerous trait-associated common genetic variants, frequently localized to regulatory DNA. We found that common genetic variation at BCL11A associated with fetal hemoglobin (HbF) level lies in noncoding sequences decorated by an erythroid enhancer chromatin signature. Fine-mapping uncovers a motif-disrupting common variant associated with reduced transcription factor (TF) binding, modestly diminished BCL11A expression, and elevated HbF. The surrounding sequences function in vivo as a developmental stage-specific, lineage-restricted enhancer. Genome engineering reveals the enhancer is required in erythroid but not B-lymphoid cells for BCL11A expression. These findings illustrate how GWASs may expose functional variants of modest impact within causal elements essential for appropriate gene expression. We propose the GWAS-marked BCL11A enhancer represents an attractive target for therapeutic genome engineering for the β-hemoglobinopathies.